2015
DOI: 10.3389/fpls.2015.01032
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis of Seed Germination and Seedling Vigor in Brassica rapa Reveals QTL Hotspots and Epistatic Interactions

Abstract: The genetic basis of seed germination and seedling vigor is largely unknown in Brassica species. We performed a study to evaluate the genetic basis of these important traits in a B. rapa doubled haploid population from a cross of a yellow-seeded oil-type yellow sarson and a black-seeded vegetable-type pak choi. We identified 26 QTL regions across all 10 linkage groups for traits related to seed weight, seed germination and seedling vigor under non-stress and salt stress conditions illustrating the polygenic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 58 publications
4
27
2
Order By: Relevance
“…Therefore, this approach not only detects the expression of a specific gene and the genotype at that gene's locus, but it also reveals clustered trans -eQTLs that are simultaneously regulated by a large fraction of the transcriptome (Brem et al, 2002; Schadt et al, 2003; Morley et al, 2004). This approach has been successfully used in crop plants to detect transcript-level variation and downstream phenotypic trait variation (Jordan et al, 2007; Shi et al, 2007; West et al, 2007; Potokina et al, 2008; Xiao et al, 2013, 2014; Del Carpio et al, 2014; Basnet et al, 2015, 2016). Although eQTLs have successfully been cloned in plants (Werner et al, 2005; Zhang et al, 2006), global eQTL analysis in a large mapping population of plants has not hitherto been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this approach not only detects the expression of a specific gene and the genotype at that gene's locus, but it also reveals clustered trans -eQTLs that are simultaneously regulated by a large fraction of the transcriptome (Brem et al, 2002; Schadt et al, 2003; Morley et al, 2004). This approach has been successfully used in crop plants to detect transcript-level variation and downstream phenotypic trait variation (Jordan et al, 2007; Shi et al, 2007; West et al, 2007; Potokina et al, 2008; Xiao et al, 2013, 2014; Del Carpio et al, 2014; Basnet et al, 2015, 2016). Although eQTLs have successfully been cloned in plants (Werner et al, 2005; Zhang et al, 2006), global eQTL analysis in a large mapping population of plants has not hitherto been performed.…”
Section: Introductionmentioning
confidence: 99%
“…To detect the QTL for these traits, Silva Pereira et al 2020). In QTL mapping for either the traditional or molecular traits, it has been observed that QTL are highly abundant in some of the genomic regions, and that QTL responsible for correlated traits are frequently clustered closely together in some specific genetic regions as compared to other regions (Goffinet and Gerber 2000;Schadt et al 2003;Chardon et al 2004;West et al 2007;Breitling et al 2008;Wu et al 2008;Wang et al 2014;Basnet et al 2015;Yang et al 2019). These regions enriched in QTL are referred to as QTL hotspots, and, statistically, they harbor a significantly higher number of QTL than expected by random chance.…”
Section: Introductionmentioning
confidence: 99%
“…However, success in improving salt tolerance in rice is made by identifying a major quantitative trait locus (QTL), which contributes to salt tolerance in rice. QTL analysis of seed germination have been reported in rice [ 18 ], soybean [ 19 ], wheat [ 20 ], Arabidopsis [ 21 ], and Brassica rapa [ 22 ]. However, it is difficult to develop rice elite varieties with a high level of salt tolerance due to a lack of understanding the mechanisms of salt tolerance during the seed germination stage.…”
Section: Introductionmentioning
confidence: 99%